Apolipoprotein A‐I Modulates Atherosclerosis Through Lymphatic Vessel‐Dependent Mechanisms in Mice - Andreea Milasan; Gabriel Jean; François Dallaire; Jean‐Claude Tardif; Yahye Merhi; Mary Sorci‐Thomas; Catherine Martel (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2017)
BackgroundSubcutaneously injected lipid‐free apoA‐I (apolipoprotein A‐I) reduces accumulation of lipid and immune cells within the aortic root of hypercholesterolemic mice without increasing high‐density lipoprotein–cholesterol concentrations. Lymphatic vessels are now recognized as prerequisite players in the modulation of cholesterol removal from the artery wall in experimental conditions of plaque regression, and particular attention has been brought to the role of the collecting lymphatic vessels in early atherosclerosis‐related lymphatic dysfunction. In the present study, we address whether and how preservation of collecting lymphatic function contributes to the protective effect of apoA‐I. Methods and ResultsAtherosclerotic Ldlr−/− mice treated with low‐dose lipid‐free apoA‐I showed enhanced lymphatic transport and abrogated collecting lymphatic vessel permeability in atherosclerotic Ldlr−/− mice when compared with albumin‐control mice. Treatment of human lymphatic endothelial cells with apoA‐I increased the adhesion of human platelets on lymphatic endothelial cells, in a bridge‐like manner, a mechanism that could strengthen endothelial cell–cell junctions and limit atherosclerosis‐associated collecting lymphatic vessel dysfunction. Experiments performed with blood platelets isolated from apoA‐I‐treated Ldlr−/− mice revealed that apoA‐I decreased ex vivo platelet aggregation. This suggests that in vivo apoA‐I treatment limits platelet thrombotic potential in blood while maintaining the platelet activity needed to sustain adequate lymphatic function. ConclusionsAltogether, we bring forward a new pleiotropic role for apoA‐I in lymphatic function and unveil new potential therapeutic targets for the prevention and treatment of atherosclerosis.